Concentrations of urinary pesticide metabolites in small-scale farmers in Chiang Mai Province, Thailand - Panuwet P. (2014)
Our research goal was to assess exposure to currently used pesticides among small-scale male farmers residing in two topographically different areas in Chiang Mai Province, Thailand. Farmers (N = 136) were recruited from Pong Yaeng subdistrict (N = 67) and Inthakhin subdistrict (N = 69). Each farmer provided a morning urine void for the analysis of 30 urinary metabolites of insecticides, herbicides, and fungicides. Farmers in Pong Yaeng had significantly higher urinary concentrations of metabolites of organophosphorus insecticides and ethylene bisdithiocarbamates, while farmers from Inthakhin had significantly higher concentrations of malathion, 2,4-D, alachlor, and parathion or EPN metabolites. Based upon the metabolites measured in the urine of the farmers, chlorpyrifos and pyrethroid insecticides seemed to be commonly used across both communities; no significant differences in metabolite concentrations of these insecticides were observed between the two farmer groups. The presence of methamidaphos in the urine of farmers suggests that, despite a ban on its use, methamidaphos continues to be used in the communities. A similar finding with metabolites of methyl parathion must be further investigated. Overall, our results suggest that while each community may use different pesticides, Thai farmers are exposed to a wide variety of pesticides with a broad range in exposure magnitude. Furthermore, age, field size, crop production type, and the use of protective equipment were found to be potential factors influencing the degree of exposure. © 2008 Elsevier B.V.